2012
DOI: 10.1002/ejoc.201200194
|View full text |Cite
|
Sign up to set email alerts
|

C3v‐Symmetrical Tribenzotriquinacenes Bearing Six Benzylic Tentacle Groups at the Molecular Periphery

Abstract: The synthesis and characterization of several C3v‐symmetrically extended tribenzotriquinacenes (TBTQs) bearing six benzylic C1‐tentacular functional groups at the arene periphery were reported. A new C3v‐symmetrical hexakis(chloromethyl)‐substituted TBTQ derivative was used as the key intermediate, and other derivatives were synthesized with high efficiency by either sixfold nucleophilic substitution reactions with phenols or sixfold Friedel–Crafts alkylation reactions with various arenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In view of the poor solubility of some extended TBTQ derivatives,17a the sixfold chloromethylated 4b,8b,12b‐tripropyl‐12d‐methyl congener 3 was chosen as a starting point (Scheme ) 25c. According to a procedure reported previously,25a treatment of 3 with sodium sulfide under phase‐transfer catalysis (PTC) conditions furnished the corresponding threefold thioether 4 in moderate yield.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of the poor solubility of some extended TBTQ derivatives,17a the sixfold chloromethylated 4b,8b,12b‐tripropyl‐12d‐methyl congener 3 was chosen as a starting point (Scheme ) 25c. According to a procedure reported previously,25a treatment of 3 with sodium sulfide under phase‐transfer catalysis (PTC) conditions furnished the corresponding threefold thioether 4 in moderate yield.…”
Section: Resultsmentioning
confidence: 99%
“…5b‐Methyl‐4b,9b,14b‐tri‐ n ‐propyl‐4b,6,8,9b,11,13,14b,15b‐octahydro‐1 H ,3 H ‐[2]benzothieno[5′,6′:5,6]thieno[3′′,4′′:5′,6′]indeno‐[1′,2′,3′:3,4]pentaleno[1,2‐ f ][2]benzothiophene (4) : A solution of the sixfold benzyl chloride 3 25c (500 mg, 0.710 mmol) and hexadecyltrimethylammonium bromide (193 mg, 0.532 mmol) in anhydrous dichloromethane (50 mL) was stirred under argon while a solution of sodium sulfide nonahydrate (768 mg, 3.20 mmol) in demineralized water (50 mL) was added dropwise through a dropping funnel. The resulting milky mixture was vigorously stirred in the dark at ambient temperature for 24 h. The organic layer was separated and the aqueous layer was extracted with dichloromethane (3×25 mL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] Derivatives of TBTQ belong to the centropolyindane family and have ah ighly (C 3v -) symmetrical aromatic carbon framework with three indane wings oriented orthogonally to each other (Figure 1). [17] It was therefore envisaged that properly multi-functionalized TBTQ derivatives, such as the 2,3,6,7,10,11-hexakis(chloromethyl)-TBTQ derivatives 2a [18] or 2b [19] can be versatile synthetic intermediates for the formation of different types of cage molecules. We previously reported that compounds 2a or 2b underwents ix-fold substitution reactions with different nucleophiles to form six-fold TBTQ derivatives, such as 3a-3d.…”
Section: Introductionmentioning
confidence: 99%
“…The C 3 v ‐symmetrical, bowl‐shaped structure11,12 and the “Cartesian” geometry1b of the TBTQ scaffold and the diverse and well controllable chemical reactivity of the TBTQ hydrocarbons [1,4,11,13,14] enables a large range of intriguing extensions, which may lead to novel applications as nanoscaled building blocks and supramolecular hosts. [1a,3a,3c,15–18] In recent years, extension of the TBTQ skeleton has mainly been focused on the elongation and enlargement of the three indane wings 1921. For example, threefold linear extension of the three independent aromatic π‐electron systems by using various condensation [4a,13a,13c,13g,15–18,19] and Diels–Alder methodologies20,21 have been pursued to enlarge the convex‐concave surface of the TBTQ core.…”
Section: Introductionmentioning
confidence: 99%